Commentary on Community Mental Health and the Common Good. (July 2017) - Arrigo, Bruce; Davidson, Larry
Abstract: This article comments on the core question addressed by this Special Issue: "What's good about public sector mental health?" Theoretical, empirical, and programmatic insights derived from the Issue's six article contributions guide the overall commentary. Several points of thematic overlap are featured in these preliminary observations, and these themes are suggestive for directing future research (e.g., citizenship studies) in the field of community mental health. Copyright © 2017 John Wiley & Sons, Ltd.